1988
DOI: 10.1111/j.1744-7348.1988.tb02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the transmission of barley yellow mosaic virus (BaYMV) by the fungus Polymyxa graminis

Abstract: S U M M A R YResting spores (cystosori) of Polymyxa graminis, selected from roots of barley plants infected with barley yellow mosaic virus (BaYMV), were used to start monofungal sand cultures. Out of 20 attempts using over 800 cystosori, P. graminis became established in 12, and in two of these BaYMV symptoms also occurred.BaYMV was detected by ELISA in extracts of dried roots heavily infected with cystosori and in zoospores of P. graminis. Calculations suggested that, on average, each zoospore carried less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…This suggests that the 73 kDa protein may be important for enabling the transmission of BaMMV by its natural vector. This hypothesis is supported by the findings of Adams et al (1988) who have demonstrated that repeated mechanical transmission of the Streatley isolate of barley yellow mosaic virus, which has now been classified as BaMMV (Andersen et al~ 1993), resulted in a strain that could not be acquired and/or transmitted by the vector. It seems reasonable to speculate that the 73 kDa protein possesses at least one additional function because all the deletions known so far are restricted to the C-terminal half of the protein.…”
Section: P2t>supporting
confidence: 73%
“…This suggests that the 73 kDa protein may be important for enabling the transmission of BaMMV by its natural vector. This hypothesis is supported by the findings of Adams et al (1988) who have demonstrated that repeated mechanical transmission of the Streatley isolate of barley yellow mosaic virus, which has now been classified as BaMMV (Andersen et al~ 1993), resulted in a strain that could not be acquired and/or transmitted by the vector. It seems reasonable to speculate that the 73 kDa protein possesses at least one additional function because all the deletions known so far are restricted to the C-terminal half of the protein.…”
Section: P2t>supporting
confidence: 73%
“…Barley mild mosaic virus (BaMMV) (Rao and Brakke 1969;Adams et al 1988). Virus acquisition occurs as the fungus develops within a virus-infected host cell, even within the first vegetative generation of the vector (Campbell and Grogan 1964).…”
Section: P Graminis-soilborne Wheat Mosaic Virus (Sbwmv) Andmentioning
confidence: 99%
“…Barley yellow mosaic virus (BaYMV-1, BaYMV-2) and barley mild mosaic virus (BaMMV) (Adams et al, 1988) from where they spread systemically throughout the plant. Due to the soil-borne transmission of the viruses, barley plants cannot be protected by chemical means and cultivation of winter barley in infested areas depends entirely on the availability of disease-resistant cultivars.…”
Section: Introductionmentioning
confidence: 99%